ANALISIS KEMAMPUAN SISWA DALAM MENJAWAB SOAL HOTS PADA METERI DINAMIKA KEPENDUDUKAN DIINDONESIA - Tri Desi Lestari; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
Research on the background of the HOTS demands of students to think at a high level in answering HOTS standard questions. Was chosen in the material dynamics of population in Indonesia because it has a fairly wide scope. Based on preliminary observations it is known that students' ability to answer is still low. . The purpose of this study was to analyze the students' ability to answer HOTS questions. This study used a quantitative descriptive method and the research instrument was a question sheet. The results of research in class XI ips SMAN 3 Tambusai showed that the students' ability to answer HOTS standard questions on objective questions was included in the medium ability category while on essay questions for low-ability students. understand the problem.